2008
DOI: 10.1080/09524622.2008.9753801
|View full text |Cite
|
Sign up to set email alerts
|

Fin Whales Avoid Loud Rhythmic Low- Frequency Sounds in the Ligurian Sea

Abstract: M. (2006a). Relative abundance of bottlenose dolphins (Tursiops sp.) exposed to long-term anthropogenic disturbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This is because the creation of man-made structures, dredging, or the building of permanent structures can not only change the biotic and abiotic components of an ecosystem, but also the acoustic landscape that characterizes it, thus also altering its ecology. Indeed, during the course of these activities, large amounts of mechanical energy can be spread, contributing to: an increase in stress factors for aquaculture species, the displacement of wild species, or the estrangement of one or more species from protected areas (Wysocki et al, 2006;Borsani et al, 2008;Filiciotto et al, 2013;Firestone 2 and Jarvis 3, 2007;Mitson and Knudsen, 2003). Other physical perturbation, which can be connected to maritime shipping and underwater acoustic equipment, can interfere in a more or less significant manner with all the activities identified by Art.…”
Section: Resultsmentioning
confidence: 99%
“…This is because the creation of man-made structures, dredging, or the building of permanent structures can not only change the biotic and abiotic components of an ecosystem, but also the acoustic landscape that characterizes it, thus also altering its ecology. Indeed, during the course of these activities, large amounts of mechanical energy can be spread, contributing to: an increase in stress factors for aquaculture species, the displacement of wild species, or the estrangement of one or more species from protected areas (Wysocki et al, 2006;Borsani et al, 2008;Filiciotto et al, 2013;Firestone 2 and Jarvis 3, 2007;Mitson and Knudsen, 2003). Other physical perturbation, which can be connected to maritime shipping and underwater acoustic equipment, can interfere in a more or less significant manner with all the activities identified by Art.…”
Section: Resultsmentioning
confidence: 99%
“…This absence of the species could be correlated with typical airgun array noise observed at measurement locations in the Ligurian Sea [24]. The measurements were used to derive the position of the sound source, which was determined to be near the French Îles d'Hyères outside Toulon [24]. Figure 12a shows the study region for this test case and the locations of the measurement positions and the estimated source location.…”
Section: Case Study: Airgun Array In the Mediterranean Seamentioning
confidence: 86%
“…Multiple whale-watching companies noticed and reported the absence of fin whales (Balaenoptera physalus) for a period of 2 months in 2002. This absence of the species could be correlated with typical airgun array noise observed at measurement locations in the Ligurian Sea [24]. The measurements were used to derive the position of the sound source, which was determined to be near the French Îles d'Hyères outside Toulon [24].…”
Section: Case Study: Airgun Array In the Mediterranean Seamentioning
confidence: 90%
“…In [11], which measured and modeled pile driving noise from a large number of points around Australia, an acoustic propagation model was proposed that allowed these results to be extrapolated to other locations. Another example, [12], on pile driving in the Ligurian Sea, found that fin whales ( Balaenoptera physalus ) avoided areas with impulsive noise. Another study, [13].…”
Section: Introductionmentioning
confidence: 99%